Acute Noise Exposure Is Associated With Intrinsic Apoptosis in Murine Central Auditory Pathway - Gröschel, Moritz; Basta, Dietmar; Ernst, Arne; Mazurek, Birgit; Szczepek, Agnieszka J. (Frontiers in Neuroscience, 2018)
Noise that is capable of inducing the hearing loss (NIHL) has a strong impact on the inner ear structures and causes early and most obvious pathophysiological changes in the auditory periphery. Several studies indicated that intrinsic apoptotic cell death mechanisms are the key factors inducing cellular degeneration immediately after noise exposure and are maintained for days or even weeks. In addition, studies demonstrated several changes in the central auditory system following noise exposure, consistent with early apoptosis-related pathologies. To clarify the underlying mechanisms, the present study focused on the noise-induced gene and protein expression of the pro-apoptotic protease activating factor-1 (APAF1) and the anti-apoptotic B-cell lymphoma 2 related protein a1a (BCL2A1A) in the cochlear nucleus (CN), inferior colliculus (IC) and auditory cortex (AC) of the murine central auditory pathway. The expression of Bcl2a1a mRNA was upregulated immediately after trauma in all tissues investigated, whereas the protein levels were significantly reduced at least in the auditory brainstem. Conversely, acute noise has decreased the expression of Apaf1 gene along the auditory pathway. The changes in APAF1 protein level were not statistically significant. It is tempting to speculate that the acoustic overstimulation leads to mitochondrial dysfunction and induction of apoptosis by regulation of proapoptotic and antiapoptotic proteins. The inverse expression pattern on the mRNA level of both genes might reflect a protective response to decrease cellular damage. Our results indicate the immediate presence of intrinsic apoptosis following noise trauma. This, in turn, may significantly contribute to the development of central structural deficits. Auditory pathway-specific inhibition of intrinsic apoptosis could be a therapeutic approach for the treatment of acute (noise-induced) hearing loss to prevent irreversible neuronal injury in auditory brain structures and to avoid profound deficits in complex auditory processing.